SEROEPIDEMIOLOGICAL STUDY OF TOXOPLASMA GONDII INFECTION AMONG WOMEN OF CHILD BEARING AGE - Lodhi, M. Saqib; Khan, M. A slam; Ahmed, Manzoor (Journal of Ayub Medical College Abbottabad, 1993)
ABSTRACT Sera from 735 Women of Child-bearing age (15-45 years) were tested for the presence of IgG antibodies to toxoplasma gondii by Enzyme-Linked Immunosorbent Assay (ELISA) technique, In total 263 sera (35.78%) were positive for Toxoplasma antibodies. There was gradual increase in prevalence with advancing age. Highly negative and statistically significant correlation was found between toxoplasma infection and economic status (r = -0.947; p<0.02). Identical result was revealed between educational status and toxo infection (P<0.05). There was no statistically significant difference between married and un married groups as far as prevalence of Toxoplasma antibodies was concerned. prevalence of toxoplasma infection was much higher in women who had a cat as pet at home as compared to those who did not have a pet cat P<0.05. This epidemiological model indicates that Faecal-oral spread by oocysts is the main cause of dissemination of infection in Pakistan.